Stereoselective Synthesis of S-Linked 2-Deoxy Sugars - Baryal, Kedar N.; Zhu, Jianglong (Synlett, 2014)
Stereoselective synthesis of S-linked 2-deoxysugars, potentially nonhydrolyzable mimics of naturally occurring O-linked 2-deoxy sugars, remains a challenge due to the absence of a directing group at C2. This article describes recent efforts in the stereoselective synthesis of S-linked 2-deoxy sugars, including our approach which involves sulfenylation of stereochemically defined 2-deoxyglycosyl lithiums with asymmetric sugar-derived disulfides.
Keywords: 2-deoxy sugars; glycosyl lithium; glycosylation; thioglycosides; umpolung